Preparation of tungsten-containing stainless steel gradient material

By using a mixed powder of 316L stainless steel and tungsten powder in additive manufacturing, adjusting the tungsten content and controlling the laser beam process parameters, the problems of brittle intermediate compounds generated by low melting points and narrow density gradient ranges in traditional materials are solved, and high The preparation of tungsten-containing stainless steel gradient materials with density and complex structures improves the mechanical properties and density control capabilities of the materials.

CN119287243APending Publication Date: 2025-01-10NINGBO UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411465494.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In additive manufacturing, traditional aluminum and titanium materials are prone to produce brittle intermediate compounds during laser scanning due to their low melting points, resulting in cracks in gradient materials and a narrow density gradient range, which cannot meet the application needs of high-density materials.

Method used

By using a mixed powder of 316L stainless steel and tungsten powder, the tungsten content is adjusted to achieve smooth changes in the density gradient. The melting and bonding effect of 316L is used to avoid tungsten melting, and the process parameters of the laser beam are controlled to form a high-density tungsten-containing stainless steel gradient material with high density tungsten-containing stainless steel gradient material .

Benefits of technology

It realizes precise regulation of the density of gradient materials over a wider range, avoids the formation of brittle intermediate compounds, is suitable for application fields of high density and complex structures, and improves the mechanical properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287243A_ABST
    Figure CN119287243A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of a tungsten-containing stainless steel gradient material. The method mainly comprises the following steps: obtaining mixed powder which is composed of 316L stainless steel powder and tungsten powder and has a plurality of different weight ratios, and applying the mixed powder to a forming substrate layer by layer according to a gradient change sequence to form powder layers, and controlling a laser beam to perform selective melting matched with the process parameters on the powder layer along a preset scanning path so as to form a consolidated gradient material part. Smooth change of the density gradient is achieved by adjusting the tungsten content, formation of cracks and brittle compounds in a traditional printing technology is avoided, the density of the gradient material can be accurately adjusted and controlled within a wider range, and the method is particularly suitable for the application field with the requirement for high density and the complex internal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of material preparation, and more particularly to the preparation of tungsten-containing stainless steel gradient materials. Background Art

[0002] In the field of additive manufacturing (AM), especially laser powder bed fusion (LPBF) technology, the manufacture of materials with density gradients has attracted more and more attention. Such gradient materials can achieve a gradual transition of different densities within the parts, thereby improving structural performance, reducing weight, and meeting special mechanical or physical performance requirements, such as complex functional parts in the defense industry, aerospace, automotive manufacturing, and medical devices.

[0003] Traditionally, light metal materials such as aluminum (Al) and titanium (Ti) are often used as gradient materials in additive manufacturing. However, in the LPBF process, these materials have low melting points and are prone to melting and metallurgical reactions during laser scanning, producing a large number of brittle intermediate compounds. These intermediate compounds often cause cracks in the prepared gradient materials, affecting the mechanical properties of the final components, and in severe cases, leading to failure in the preparation of gradient materials. In addition, due to their low density, metals such as aluminum and titanium can achieve a narrow range of density gradients, which cannot meet certain application scenarios that require high-density materials.

[0004] Therefore, how to avoid the formation of brittle intermediate compounds, broaden the density control range of gradient materials, and achieve the effective combination of high melting point and low melting point materials has become the main challenge facing current technology. Summary of the invention

[0005] The present disclosure proposes a preparation method for a tungsten-containing stainless steel gradient material. By adjusting the tungsten content, a smooth change in density gradient is achieved, thereby avoiding the formation of cracks and brittle compounds in traditional printing technology. The density of the gradient material can be accurately controlled within a wider range, and is particularly suitable for application fields that require high density and complex internal structures.

[0006] In a first aspect, the present disclosure provides a method for preparing a tungsten-containing stainless steel gradient material, comprising: obtaining a mixed powder having a plurality of different weight ratios composed of 316L stainless steel powder and tungsten powder; applying the plurality of mixed powders having different weight ratios layer by layer on a forming substrate in a gradient change order to form a powder layer, and controlling a laser beam to selectively melt the powder layer along a preset scanning path in a manner matching process parameters to form a consolidated gradient material part; wherein the process parameters are set such that under the action of the laser beam, the 316L stainless steel powder melts, while the tungsten powder remains in an unmelted state.

[0007] Preferably, each weight ratio of the mixed powder is used to form one or more powder layers.

[0008] Preferably, at least in the scanning area of ​​one or more of the powder layers there are a plurality of mixed powders with different weight ratios.

[0009] Preferably, the 316L stainless steel powder and tungsten powder are respectively selected as spherical powders with a particle size of 15 to 53 μm.

[0010] Preferably, the forming substrate is selected to be 316L stainless steel. Before applying the mixed powder, the method further comprises: applying at least a first layer of the obtained 316L stainless steel powder on the forming substrate, and controlling the laser beam to selectively melt the first layer along a preset scanning path in a manner matching the process parameters to form a bonding layer attached to the forming substrate.

[0011] Preferably, the weight ratio of the tungsten powder in the mixed powder is 0-90wt%.

[0012] Preferably, the process parameters include one or more of a layer thickness of 20-40 μm, a scanning interval of 80-120 μm, a laser power of 150-190 W, and a scanning speed of 800-1200 mm / s.

[0013] Preferably, the gradient change sequence of the mixed powder is determined according to a preset material density gradient change sequence.

[0014] In a second aspect, the present disclosure provides a tungsten-containing stainless steel gradient material obtained by the method described in any one of the first aspects.

[0015] Preferably, the density of the gradient material is in the range of 8-17 g / cm 3 .

[0016] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings, which are incorporated herein and form a part of the specification, illustrate one or more embodiments of the present disclosure and, together with the description, serve to explain the principles of the present disclosure and to enable one of ordinary skill in the relevant art to make and use the present disclosure.

[0018] Figure 1 A flow chart of a method for preparing a tungsten-containing stainless steel gradient material according to an embodiment of the present disclosure is shown;

[0019] Figure 2 A schematic diagram showing a plurality of mixed powders corresponding to a layer cross section according to an embodiment of the present disclosure;

[0020] Figure 3Another schematic diagram showing a plurality of mixed powders corresponding to a layer cross section according to an embodiment of the present disclosure;

[0021] Figure 4 A schematic diagram of an additive manufacturing device according to an embodiment of the present disclosure is shown;

[0022] Figure 5 SEM images of samples prepared according to Comparative Examples 5 to 10 are shown;

[0023] Figure 6 The density comparison images of the samples prepared before and after the process parameter optimization according to Comparative Examples 1 to 4 are shown;

[0024] Figure 7 Shows microstructure images according to Comparative Examples 1 to 4 and Comparative Examples 11 and 13;

[0025] Figure 8 The morphological characteristics of the prepared Ti-Al gradient material and the actual sample picture are shown;

[0026] Fig. 9 SEM images of single-layer samples prepared according to Examples 1 to 9 at a scale of 200 μm are shown;

[0027] Fig.10 SEM images of single-layer samples prepared according to Examples 1 to 9 at a scale of 500 μm are shown;

[0028] Fig.11 The microstructure distribution diagrams of the single-layer samples prepared according to Example 1.1 and Examples 1 to 4 in the XY section and the XZ section are shown respectively;

[0029] Fig.12 An SEM image of a gradient sample prepared according to Example 11 is shown. DETAILED DESCRIPTION

[0030] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments may be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; rather, the description of these embodiments is intended to make the present disclosure more comprehensive and complete and to fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a deeper understanding of the embodiments of the present disclosure.

[0031] The "additive manufacturing (AM)" described in this disclosure is a 3D printing technology that builds parts by adding powder materials layer by layer and melting the powder materials with a laser beam. This technology is based on a digital model generated by computer-aided design (CAD) software, and accurately controls the melting and solidification process of each layer of material, thereby gradually building a complete part.

[0032] The present disclosure generally relates to manufacturing a density gradient material by using stainless steel (316L) and tungsten (W), utilizing the melt bonding effect of 316L to avoid the melting of tungsten and the formation of intermediate compounds, thereby achieving the regulation of a wide density gradient. Figure 1 FIG. 1 shows a flow chart of a method for preparing a tungsten-containing stainless steel gradient material according to an embodiment of the present disclosure. Figure 1 As shown, the overall implementation of the method for preparing the gradient material is shown below.

[0033] (1) Preparation of mixed powder

[0034] In the implementation process of the present disclosure, the mixed powder used is composed of 316L powder and W powder, and these powders are mixed according to predetermined different weight ratios. In a specific implementation, 316L powder and pure W powder with a particle size range of 15-53 μm are selected, and both powders are spherical particles to ensure that they have good fluidity and uniform distribution characteristics in the laser powder bed fusion (LPBF) process.

[0035] The mass of 316L powder and W powder is accurately weighed (powder purity ≧ 99.95%) by a high-precision electronic scale in strict accordance with the predetermined weight ratio. The accuracy of the ratio must be ensured during the weighing process because the ratio directly affects the density of the final gradient material. The weight ratio range of W powder in the mixed powder can be selected from 0 to 90 Wt%. For example, in some specific embodiments, the weight ratio of W powder can be selected as 0 Wt%, 10 Wt%, 20 Wt%, 30 Wt%, 40 Wt%, 50 Wt%, 60 Wt%, 70 Wt%, 80 Wt% and 90 Wt%, respectively, and the material density is gradually changed by adjusting the ratio.

[0036] After the powders are weighed, the powders are mixed by a planetary ball mill. The planetary ball mill is used to fully mix the 316L powder with the W powder. The principle is to use the centrifugal force generated by high-speed rotation to make the powders collide, shear and roll with each other inside the container, so as to achieve the purpose of uniform mixing. In the specific implementation of the present disclosure, the mixing parameters of the ball mill are set as follows: the rotation speed is 200rmp / min, each operation is 15min, and the pause is 5min. To ensure uniform mixing, it is set to bidirectional rotation, that is, the ball mill alternates in forward and reverse directions, runs in each direction for 15min, and repeats 8 cycles to prevent powder agglomeration and avoid excessive grinding, so that the particle size and morphology of the mixed powder do not change significantly. During the ball milling process, the mixing environment must be kept dry and clean to avoid moisture absorption or contamination of the powder. After the mixing is completed, the powder sample is taken out and placed in a vacuum drying device for drying to remove moisture or impurities introduced during the mixing process to ensure that the powder will not affect the forming effect due to moisture in the subsequent additive manufacturing process. The drying process is generally carried out in a vacuum environment at 60°C to 80°C for several hours (e.g., 2~4h) until the moisture content of the powder drops to within the range required by the process, thereby obtaining the required mixed powder with good fluidity and uniformity for subsequent additive manufacturing.

[0037] (2) Mixed powder is applied in a gradient order

[0038] In the additive manufacturing process, the order in which mixed powders with different weight ratios are applied has an important influence on the density distribution of the final gradient material. Therefore, before implementing additive manufacturing, it is necessary to set a reasonable application order for mixed powders with different weight ratios to ensure that the gradient change of material density achieves the expected effect.

[0039] In some embodiments, each weight ratio of the mixed powder may be applied separately to form one or more powder layers.

[0040] Figure 2 A schematic diagram of a plurality of mixed powders corresponding to a layer cross section according to an embodiment of the present disclosure is shown. Figure 2 As shown, the additively manufactured part is divided into layers with cross sections S1-S n , each layer section corresponds to an applied powder layer. Set the mixed powder to have T1-T n The weight ratio of the mixed powder is set to a gradient, and the order of applying the mixed powder is set so that each weight ratio of the mixed powder can correspond to one or more layer sections (i.e., powder layers). Taking the former (corresponding to one layer section) as an example, T1 corresponds to S1, T2 corresponds to S2, and so on; taking the latter (corresponding to multiple layer sections) as an example, T1 can correspond to S1-S n A section of a layer in the middle, and vice versa.

[0041] Taking the additive manufacturing equipment (3D printer) with a powder cylinder for powder feeding as an example, during the application of the mixed powder, after each gradient (i.e., a specific ratio) of mixed powder is printed, the powder cylinder needs to be replaced to ensure that during the application process of different levels, the required weight ratio of mixed powder can be provided according to the design requirements until the printing of all gradients of mixed powder is completed.

[0042] In a specific powder replacement process, the printing process of the equipment needs to be observed first, especially when printing the last layer of mixed powder of the current weight ratio. In order to ensure the quality of each layer of printing, the operator needs to pause the equipment in advance and wait for the end of the printing task. At this time, the equipment will continue to complete the printing task of the last layer to ensure that the quality of the current layer is not affected. When the equipment completes the task of the last layer, the printing process will automatically stop and enter the exhaust stage. At this stage, a certain air pressure needs to be maintained in the cabin of the equipment to ensure the safety and smoothness of the next operation, until the air pressure in the cabin drops to the standard atmospheric pressure, and the cabin door can be opened for subsequent cleaning. Use a powder suction machine to clean the powder cylinder and the powder spreading device to remove residual powder. After the powder cleaning is completed, the height of the forming cylinder is manually lowered, usually by the thickness of one layer of powder, to prepare the corresponding powder spreading thickness for the next weight ratio of mixed powder to be carried out, to ensure that each layer of powder is applied evenly and in accordance with the design requirements. The operator also needs to lower the powder cylinder to a suitable height according to the height of the next gradient printing, usually three times the height of the next weight ratio printing, to ensure that the mixed powder inside the powder cylinder can be smoothly spread onto the forming substrate. Finally, the next weight ratio of mixed powder is poured into the powder tank, and the equipment enters the next gradient printing task until all gradients of mixed powder printing are completed.

[0043] In some embodiments, at least in the scanning area of ​​one or more powder layers, there are multiple mixed powders with different weight ratios.

[0044] Figure 3 Another schematic diagram of a plurality of mixed powders corresponding to a layer cross section according to an embodiment of the present disclosure is shown. Figure 3 As shown, in one of the powder layers constituting the powder bed, the scanning area (the area corresponding to the layer cross section) is set to have a plurality of mixed powders with different weight ratios, that is, in addition to Figure 2 In addition to the gradient distribution of the mixed powder set in the vertical direction, a gradient distribution in the horizontal direction can also be set in any powder layer within a range that at least covers the scanning area. It should be understood that since the powder outside the scanning area is not affected by the laser beam, it is not within the consideration range of the gradient distribution setting. The powder outside the scanning area can be applied as a mixed powder or 316L powder with any weight ratio.

[0045] exist Figure 3In the specific powder application application, the additive manufacturing equipment can use the method of feeding powder from above to release the corresponding mixed powder to different areas of the forming substrate through different powder containers. In one implementation, for example, a plurality of powder containers that can be moved under driving (for example, driven by a mechanical arm or an electric slide rail) are provided in the cabin of the equipment, and mixed powders of different weight ratios are stored in each container. The powder in each container is pre-configured according to the design requirements to meet the material properties required for subsequent printing. During the printing process, the control system automatically adjusts the release port of each container according to the set scanning path and the preset powder ratio, so that each container can release the corresponding mixed powder in different areas of the same layer. As the equipment works, multiple powder containers will release mixed powder to the corresponding areas of the forming substrate at the same time, and mixed powders of various weight ratios are evenly covered in the scanning area by gravity. After the different mixed powders are applied, the applied powder layer can be further rolled using a powder spreading device (such as a roller) to achieve the application of evenly spread mixed powders of different weight ratios in different areas of the same powder layer (especially the scanning area).

[0046] In some embodiments, the gradient change order of the mixed powder is determined according to the pre-set material density gradient change order. The setting of the density gradient change order is based on the comprehensive consideration of the functional requirements and material structure of the target material. Generally speaking, the density gradient change order can gradually transition from low density to high density, or change nonlinearly according to the use environment and structural requirements. This pre-set density gradient determines the application order of 316L and W mixed powders and the adjustment of the corresponding weight ratio during the additive manufacturing process.

[0047] Specifically, the required density gradient distribution is first designed according to the functional requirements of the target part. For example, if the part needs to have a gradually increasing density distribution, the designer will set the density of the material to gradually increase within a specific cross-sectional range. This change can be achieved by adjusting the weight ratio of 316L powder and tungsten powder, where 316L stainless steel is used as a bonding phase and tungsten is used as a non-melting high-density filling phase. By increasing the proportion of W powder, the overall density of the material is gradually increased. Based on the preset density gradient change sequence, the order in which each layer of powder is applied can be determined. For example, the layer section S1-S n In the order of, S1 represents the first layer, and S n For materials with increasing density, the initial layer (S1) may contain a relatively low tungsten content (e.g., 0 Wt%), while the powder mixture corresponding to S n The proportion of tungsten in the mixed powder corresponding to the layer gradually increases (e.g. 90 Wt%). This sequence ensures that the density of the material can be gradually increased during the printing process, and finally a gradient material with a continuous change from low to high density is obtained.

[0048] (3) Additive manufacturing of tungsten-containing stainless steel gradient materials

[0049] In the additive manufacturing process, the mixed powder obtained in step (1) is applied layer by layer on the forming substrate in the order of the gradient-changing components set in step (2) to form a powder layer. After each powder layer is applied, the laser beam is controlled to selectively melt the powder layer along a preset scanning path in a manner matching the process parameters to form a solidified layer section. This process is repeated until a gradient material part with a preset structure (pre-set 3D model) is formed.

[0050] Figure 4 A schematic diagram of an additive manufacturing device according to an embodiment of the present disclosure is shown. The additive manufacturing of the tungsten-containing stainless steel gradient material disclosed in the present disclosure is carried out in the device. A layer of mixed powder consisting of 316L powder and W powder in a specific weight ratio is applied to the forming substrate by a powder spreading device, and the weight ratio of the two is adjusted in each subsequent layer according to a preset gradient change sequence. For example, according to a predetermined design, the bottommost powder layer can have a lower W content, and as the number of layers increases, the proportion of W gradually increases, thereby achieving a gradient change in material density. After each layer of powder is applied, the control system controls the laser emitter and the galvanometer to control the laser beam to accurately scan the powder layer along a preset scanning path, and melt the powder layer with preset process parameters.

[0051] In addition, before laser melting, the loaded forming substrate needs to be leveled and the powder needs to be spread. By setting the laser power and scanning parameters for the 3D model, turn on the air inlet and outlet options, fill with inert gas (argon), and turn on the circulation option when the oxygen content is less than 1%. When the oxygen content is equal to 0, turn off the air outlet, turn on the water cooling, laser, and enable options. Click Print to start printing.

[0052] Under the action of the laser beam, the 316L powder will melt, while the W powder will remain in an unmelted state. The melted 316L powder acts as a bond, evenly wrapping and consolidating the W particles together to form a dense layer section. Since the melting point of W (about 3422°C) is much higher than that of 316L (about 1400°C), the set process parameters such as laser power, scanning speed and layer thickness ensure that W does not melt during the printing process. This difference allows the W particles to act as a high-density filling material, stably embedded in the molten phase of 316L, avoiding adverse metallurgical reactions between W and 316L, and thus avoiding the formation of brittle intermediate compounds.

[0053] In order to precisely control the melting behavior of 316L powder and avoid the melting of W, the key parameters of the additive manufacturing process such as laser power, scanning speed, layer thickness and scanning spacing are precisely adjusted. For example, the process parameters are set to include layer thickness of 20~40μm, scanning spacing of 80~120μm, laser power of 150~190W and scanning speed of 800~1200mm / s. After each layer of mixed powder is applied and laser melted, the equipment will automatically lower the height of the forming substrate to prepare for the application of the next layer of powder. The whole process is carried out in a closed environment, repeating the cycle of powder spreading and melting until all the set gradient powder layers are printed to form a complete three-dimensional structure. Since the application order and material ratio of each layer of powder are strictly carried out according to the preset density gradient, the printing process can form a gradient material part with a gradually changing density from bottom to top.

[0054] It should be understood that the present disclosure achieves uniform bonding of high-density materials through the melting of 316L and the non-melting of W. The bonding phase formed by the melting of 316L uniformly wraps the W particles, and the W particles do not chemically react with the molten 316L, thereby avoiding the formation of harmful intermediate compounds. In this way, by regulating the W content, the density of each layer of material can be precisely adjusted. In contrast, in traditional additive manufacturing processes using materials such as aluminum (Al) and titanium (Ti), aluminum and titanium will undergo metallurgical reactions to form intermediate compounds that are prone to brittle fracture, resulting in a decrease in material performance, and only achieving narrow density range regulation of gradient materials. The present disclosure avoids this problem by controlling the non-melting of W, thereby being able to produce a composite material with a wide density gradient while ensuring the structural integrity of the material.

[0055] In some embodiments, the forming substrate preferably uses 316L stainless steel material, which has the same chemical composition as the 316L stainless steel powder in the mixed powder, and can effectively promote the good bonding between the powder and the substrate. In the application process of the mixed powder, in order to ensure that a strong bonding layer is formed between the subsequent gradient material and the substrate, at least one layer of 316L stainless steel powder is usually applied to the forming substrate before applying the mixed powder as a bonding layer. In the specific operation, the obtained pure 316L powder is applied to the surface of the forming substrate, and this powder layer can also be understood as a mixed powder layer containing 0 Wt% tungsten. The main purpose of applying this layer is to fuse the forming substrate with the 316L powder layer through a laser selective melting process to form a dense bonding layer. In this way, the forming substrate and the gradient material of the upper layer will be closely combined, thereby avoiding interface defects or poor bonding problems. After the bonding layer is formed, the subsequent gradient powder layers will be applied layer by layer in a predetermined order. Since the first layer has formed a strong bonding layer, the subsequent gradient powder layers can be smoothly connected to it by laser melting, ensuring the consistency and stability of the gradient material from the substrate to the surface.

[0056] In order to better understand the present disclosure, the implementation process of the present disclosure is further described below based on detailed embodiments, but it should be understood that the present disclosure is not limited to the following embodiments.

[0057] Example 1 (single-layer preparation: 1 sample corresponds to 1 W weight ratio)

[0058] (1) Select 316L (Cr~16.99 wt%, Ni~12.85 wt%, Mo~2.835 wt%) and pure W spherical powders with a particle size of 15~53 μm. Weigh 316L powder and pure W powder according to the weight ratio of W powder to 10 wt% of the total powder and mix them using a planetary ball mill. The mixing parameters are set as follows: the speed is 200 rpm, each operation is 15 min, pause for 5 min, and bidirectional rotation is run 8 times. The two powders are fully mixed and then the powder is vacuum dried to obtain the desired mixed powder.

[0059] (2) Lower the powder cylinder to a height equal to the printing height*3, pour the mixed powder obtained in step (1) into the powder cylinder, install the forming substrate, and level and spread the powder on the substrate. Set the process parameters for the 3D model (laser power 170W, scanning speed 1000 mm / s, layer thickness 30μm, scanning spacing 100μm), turn on the air inlet and outlet options, fill with inert gas (argon), and turn on the circulation option when the oxygen content is less than 1%. When the oxygen content is equal to 0, turn off the air outlet, turn on the water cooling, laser, and enable options. Click Print to start printing until a sample (abbreviated as Fe-W) matching the 3D model structure is formed. 10 ).

[0060] Example 1.1

[0061] The steps are basically the same as those in Example 1, except that in Example 1.1, the weight ratio of W powder to the total powder is 0 Wt% (in the weighing process, only 316L powder is used, and no W powder is added), and the obtained sample is abbreviated as Fe.

[0062] Embodiment 2 to Embodiment 9

[0063] The steps are basically the same as those in Example 1, except that the weight ratio of W powder to the total powder in Examples 2 to 9 is 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt% and 90 wt%, respectively. The obtained samples are abbreviated as Fe-W 20 、Fe-W 30 、Fe-W 40 、Fe-W 50 、Fe-W 60 、Fe-W70 、Fe-W 80 、Fe-W 90 .

[0064] Example 10 (Gradient preparation: one sample corresponds to multiple W weight ratios)

[0065] (1) 316L (Cr~16.99 Wt%, Ni~12.85 Wt%, Mo~2.835 Wt%) and pure W spherical powders with a particle size of 15~53 μm were selected. 316L powder and pure W powder were weighed according to the weight ratio of W powder to the total powder of 10 Wt%, 20 Wt%, 30 Wt%, 40 Wt%, 50 Wt%, 60 Wt%, 70 Wt%, 80 Wt% and 90 Wt% respectively and mixed by a planetary ball mill. The mixing parameters were set as follows: the speed was 200 rpm, each operation was 15 min, paused for 5 min, and bidirectional rotation was run 8 times. The two powders were fully mixed and then the powders were vacuum dried to obtain the required 9 mixed powders with different weight ratios.

[0066] (2) The number of printing layers is 1000 according to the sample design height of 3 cm divided by the powder layer thickness of 30 μm. The order of applying the mixed powder is set so that each mixed powder with a weight ratio (including pure 316L powder with a W ratio of 0 Wt% for forming a bonding layer, a total of 10 kinds of powders) corresponds to 100 layers, among which pure 316L powder with a W ratio of 0 Wt% corresponds to the 1st to 100th layers, and mixed powder with W powder accounting for 10 Wt% of the total powder corresponds to the 101st to 200th layers, and so on.

[0067] (3) Lower the powder cylinder to a height equal to the current weight ratio powder layer printing height*3, pour the mixed powder obtained in step (1) into the powder cylinder, install the forming substrate, and level and test the substrate. Set the process parameters for the 3D model (laser power 170W, scanning speed 1000 mm / s, layer thickness 30μm, scanning spacing 100μm), turn on the air inlet and outlet options, fill with inert gas (argon), and turn on the circulation option when the oxygen content is less than 1%. When the oxygen content is equal to 0, turn off the air outlet, turn on the water cooling, laser, and enable options. Click Print to start printing. Whenever the last layer of a certain weight ratio is printed, pause the printing and wait for the current layer to be printed. After the printing is completed, stop the task and wait for the air to be discharged. When the air pressure in the cabin drops to the standard atmospheric pressure, open the cabin door and use a powder suction machine to clean the powder cylinder and the powder spreading device to ensure that no residual powder remains. Then manually lower the forming cylinder to a height of the powder layer thickness, and lower the powder cylinder to a height of 3 times the next weight ratio powder layer printing height. Pour the mixed powder of the corresponding weight ratio into the powder cylinder and manually control the powder spreading device to spread a layer of powder. Then repeat the previous printing steps until a sample matching the 3D model structure is formed (abbreviated as Fe-W0-90 ).

[0068] Comparative Example 1

[0069] The steps are basically the same as those in Example 1, except that the mixed powder used in Comparative Example 1 is a mixed powder composed of Al (AlSi10Mg) powder and TC4 (Ti6Al4V) powder, and the weight ratio of TC4 powder to the total powder is 5wt%. The set process parameters are: laser power 70W, scanning speed 800mm / s, layer thickness 30μm, scanning spacing 70μm, energy density 116.7 J / mm 3 The final sample obtained is abbreviated as Al-Ti5).

[0070] Comparative Example 2 to Comparative Example 13

[0071] The steps are basically the same as those in Comparative Example 1, except that the weight ratios of TC4 powder to the total powder in Comparative Examples 2 to 13 are 0 wt%, 10 wt%, 15 wt%, 20 wt%, 30 wt%, 40 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt%, 95 wt% and 100 wt%, respectively. The obtained samples are abbreviated as Al, Al-Ti, Al-Ti- 10 、Al-Ti 15 、Al-Ti 20 、Al-Ti 30 、Al-Ti 40 、Al-Ti 60 、Al-Ti 70 、Al-Ti 80 、Al-Ti 90 、Al-Ti 95 and Al-Ti 100 .

[0072] Comparative Example Results Characterization

[0073] The comparative results show that when a mixed powder consisting of Al (AlSi10Mg) powder and TC4 (Ti6Al4V) powder is used for additive manufacturing, the printing difficulty of the mixed powder gradually increases with the increase of TC4 powder content. Figure 5The SEM images of samples prepared according to Comparative Examples 5 to 10 are shown, and cracks of varying degrees can be clearly observed. In these samples, the forming process after mixing Ti and Al encountered significant challenges, especially when the weight ratio difference between the two decreased, the window of the additive manufacturing process became extremely narrow. In the comparative experiment, although the process parameters such as laser power, scanning speed, layer thickness, scanning spacing, etc. were optimized many times, and even attempts were made to improve the forming effect by adding nucleating agents, the appearance of cracks could not be avoided for the medium proportion interval containing TC4 (15%~85%). The generation of such cracks is mainly attributed to the formation of brittle intermetallic compounds between Al and Ti after melting, which leads to a sharp increase in the internal stress of the material, thereby triggering the generation of cracks. Only when the weight ratio of TC4 powder is low (less than 15%) or high (greater than 85%), a relatively crack-free formed sample can be obtained by adjusting the process parameters. Figure 6 The results of Comparative Examples 1 to 4 (samples Al, Al-Ti5, Al-Ti 10 and Al-Ti 15 ) Density comparison images of the samples prepared before and after process parameter optimization. It can be clearly seen from the comparison that after the process parameter optimization, the density of each sample has been significantly improved, especially in the mixed powder forming process with low to medium Ti content, the optimization effect is most significant.

[0074] Among them, the optimized process parameters when the weight ratio of TC4 powder is less than 15% or greater than 85% are shown in Table 1-3 below.

[0075]

[0076] Table 1: Process parameters after optimization of 95wt%AlSi10Mg +5wt%Ti6Al4V

[0077]

[0078] Table 2: Process parameters after optimization of 90wt%AlSi10Mg +10wt%Ti6Al4V

[0079]

[0080] Table 3: Process parameters after optimization of 85wt%AlSi10Mg +15wt%Ti6Al4V

[0081] In particular, when the proportion of TC4 components is less than 15%, the Ti content is too low to induce a significant phase change, so the risk of crack formation is reduced; when the TC4 content exceeds 85%, the Al content is too low to form sufficient brittle compounds, so the quality of the formed samples is effectively improved. However, when the proportion of TC4 powder is between 15% and 85%, the formation of intermetallic compounds and thermal stress during melting inevitably lead to cracking of the material, which is difficult to overcome even after optimizing the process parameters. This shows that the process window of Al-Ti in this specific ratio range is extremely narrow, and it is difficult to achieve a stable additive manufacturing process.

[0082] Figure 7 The results of Comparative Examples 1 to 4 and Comparative Examples 11 and 13 (samples Al, Al-Ti5, Al-Ti 10 、Al-Ti 15 、Al-Ti 90 and Al-Ti 100 ). The image shows the trend of the microstructure in samples with different Ti contents as the Ti content changes, and reveals the distribution of intermediate compounds. It can be seen that with the increase of Ti content, the content of intermediate compounds first gradually increases, and then gradually decreases. The intermediate compounds are unevenly distributed in the matrix, have large sizes, and are irregular in shape, which is not conducive to the performance of the material. Since the crystal structure and properties of these compounds are significantly different from those of the matrix material, they will cause stress concentration and reduce the overall toughness of the material.

[0083] Figure 8The morphological characteristics of the prepared Ti-Al gradient material and the actual sample are shown. It can be seen that when the TC4 content is between 15% and 85%, crack-free samples cannot be obtained. This is because in this content range, the mixture of Ti and Al generates brittle intermetallic compounds during the additive manufacturing process, resulting in excessive stress in the material and cracks. This phenomenon not only affects the density of the material, but also hinders the interface bonding between different components, especially in the gradient transition range. When transitioning from 15% TC4 to 85% TC4, the interface bonding becomes very difficult, mainly due to the large differences in the physical and chemical properties of the two materials, including melting point, thermal expansion coefficient, and chemical reaction activity. These differences cause significant stress concentration at the interface between the two materials and promote the formation of cracks. In addition, the high brittleness of the intermetallic compound formed after the mixture of Ti and Al further exacerbates the difficulty of interface bonding. The combination of Ti and Al is not suitable as the preferred material for preparing gradient materials with a wide range of density changes because it cannot avoid the formation of cracks in a specific content range. In order to expand the application prospects of this type of material, it is necessary to introduce other alloy elements or adopt more optimized process parameters to reduce the formation of brittle compounds and improve the bonding performance of the material interface.

[0084] Example Results Characterization

[0085] Fig. 9 SEM images of single-layer samples prepared according to Examples 1 to 9 at a scale of 200 μm are shown. The observation results show that when the W content is less than 90%, the forming quality of the Fe-W material is good and its density is relatively high. This means that at low W content, the microstructure of the material is more uniform and the porosity is lower, which improves the overall mechanical properties of the material. However, when the W content reaches 90%, the density of the sample decreases significantly, which may be due to the presence of excessive W powder, which leads to the formation of larger pores or defects during the melting process, thereby affecting the quality of the final product.

[0086] Fig.10 SEM images of single-layer samples prepared according to Examples 1 to 9 at a scale of 500 μm are shown. Through image analysis, it can be seen that in the single-layer material, the distribution of W content is relatively uniform, and there is a certain correlation between the forming quality and the W content. As the W content changes, the forming characteristics of the material will also change. The uniform distribution of the components in the material is a key factor in ensuring the consistency of the performance of the finished product, so this is particularly important in the practical application of the material.

[0087] Fig.11The microstructure distribution diagrams of the single-layer samples prepared according to Example 1.1 and Examples 1 to 4 at the XY section and XZ section are shown. It can be observed that the organizational structures on different sections are significantly different. As the W content increases, the width of the melt channel gradually increases, while the melting depth gradually decreases. This phenomenon may be due to the fact that the higher W content leads to a decrease in thermal conductivity during the laser melting process, thereby affecting the depth and width of the melting area. In addition, as the W content increases, the organizational morphology of the melt channel gradually becomes blurred, indicating that the melting and solidification process of the material at a higher W content is affected to a certain extent, and uneven solidification may occur.

[0088] Fig.12 The SEM images of the gradient samples prepared according to Example 11 are shown. The results show that high-quality gradient materials can be successfully prepared using the combination of 316L and W. The microstructure of this material is uniform and dense, showing the potential for good forming at different weight ratios.

[0089] In general, the density of the gradient material prepared in the present disclosure ranges from 8 to 17 g / cm³. Specifically, the density of the materials with a W weight ratio of 0 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt% and 90 wt% is 8 g / cm³, 8.50 g / cm³, 9.06 g / cm³, 9.71 g / cm³, 10.45 g / cm³, 11.32 g / cm³, 12.34 g / cm³, 13.57 g / cm³, 15.07 g / cm³ and 16.95 g / cm³, respectively. This data shows that by adjusting the W content, the density of the material can be effectively controlled to achieve the desired physical properties, providing greater possibilities for the design and application of the material.

[0090] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. The present disclosure is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the present disclosure is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from the scope thereof.

Claims

1. A method for preparing a tungsten-containing stainless steel gradient material, comprising: Obtaining mixed powders composed of 316L stainless steel powder and tungsten powder with multiple different weight ratios; Applying the plurality of mixed powders of different weight ratios layer by layer on a forming substrate in a gradient change order to form a powder layer, and controlling a laser beam to selectively melt the powder layer along a preset scanning path in a manner matching process parameters to form a consolidated gradient material part; The process parameters are set such that under the action of the laser beam, the 316L stainless steel powder melts, while the tungsten powder remains in an unmelted state.

2. The method according to claim 1, wherein each weight ratio of the mixed powder is used to form one or more powder layers.

3. The method according to claim 1 or 2, wherein at least in the scanning area of ​​one or more of the powder layers there are a plurality of mixed powders with different weight ratios.

4. The method according to claim 1, wherein the 316L stainless steel powder and the tungsten powder are respectively selected as spherical powders with a particle size of 15 to 53 μm.

5. The method according to claim 1, wherein the forming substrate is selected from 316L stainless steel, and before applying the mixed powder, the method further comprises: At least a first layer of the obtained 316L stainless steel powder is applied to the forming substrate, and the laser beam is controlled to selectively melt the first layer along a preset scanning path to match the process parameters to form a bonding layer attached to the forming substrate.

6. The method according to claim 1, wherein the weight ratio of the tungsten powder in the mixed powder is 0-90wt%.

7. The method according to claim 1, wherein the process parameters include one or more of a layer thickness of 20-40 μm, a scanning pitch of 80-120 μm, a laser power of 150-190 W, and a scanning speed of 800-1200 mm / s.

8. The method according to claim 1, wherein the gradient change sequence of the mixed powder is determined according to a preset material density gradient change sequence.

9. A tungsten-containing stainless steel gradient material obtained according to the method of any one of claims 1 to 8.

10. The gradient material according to claim 9, wherein the density of the gradient material is in the range of 8-17 g / cm 3 .

Citation Information

Cited By

  • Additive manufacturing gradient alloy and preparation method thereof

    CN120158746A

  • Aluminum-tungsten-based gradient composite material and preparation method thereof

    CN120394871A